2009
DOI: 10.1162/jeea.2009.7.4.858
|View full text |Cite
|
Sign up to set email alerts
|

New Evidence on the Interest Rate Effects of Budget Deficits and Debt

Abstract: Estimating the effects of government debt and deficits on Treasury yields is complicated by the need to isolate the effects of fiscal policy from other influences. To abstract from the effects of the business cycle, and associated monetary policy actions, on debt, deficits, and interest rates, this paper studies the relationship between long-horizon expected government debt and deficits, measured by CBO and OMB projections, and expected future long-term interest rates. The estimated effects of government debt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
231
4
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 479 publications
(269 citation statements)
references
References 33 publications
28
231
4
6
Order By: Relevance
“…Gale and Orszag (2003) report that out of 59 studies, 29 find that weaker fiscal variables increase interest rates, while 11 had mixed results and 19 found that the effect was not significant. Moreover, a majority of studies finds that the effect of fiscal policy on interest rates is larger when the fiscal deficit rather than public debt is included as an explanatory variable (Faini, 2006;Laubach, 2009). In addition, the effects of fiscal policy are larger when expectations of future fiscal policy rather than actual values of the debt and deficit are used (Laubach, 2009) and when single country studies rather than cross country studies are performed.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Gale and Orszag (2003) report that out of 59 studies, 29 find that weaker fiscal variables increase interest rates, while 11 had mixed results and 19 found that the effect was not significant. Moreover, a majority of studies finds that the effect of fiscal policy on interest rates is larger when the fiscal deficit rather than public debt is included as an explanatory variable (Faini, 2006;Laubach, 2009). In addition, the effects of fiscal policy are larger when expectations of future fiscal policy rather than actual values of the debt and deficit are used (Laubach, 2009) and when single country studies rather than cross country studies are performed.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Moreover, a majority of studies finds that the effect of fiscal policy on interest rates is larger when the fiscal deficit rather than public debt is included as an explanatory variable (Faini, 2006;Laubach, 2009). In addition, the effects of fiscal policy are larger when expectations of future fiscal policy rather than actual values of the debt and deficit are used (Laubach, 2009) and when single country studies rather than cross country studies are performed. The estimated impact on interest rates of a change of one percent of GDP in the fiscal deficit ranges from 10 basis points to 60 basis points (Laubach, 2009).…”
Section: Background and Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Much of the discussion has centred on the question of whether government spending will promote [1][2][3] or inhibit economic growth [4,5]. Critics of government spending argue, first, that such spending has an immediate effect of increasing debt which, if associated with a loss of confidence by investors, will also increase the cost of servicing that debt as a consequence of increased interest rates [6,7]. Second, they argue that, by "crowding out" private markets and, by implication, their assumed greater efficiency, they will inhibit the growth necessary for recovery [8].…”
Section: Introductionmentioning
confidence: 99%